2020
DOI: 10.31186/jenggano.5.1.1-10
|View full text |Cite
|
Sign up to set email alerts
|

POTENSI ISOLAT Bacillus sp. ENG-4 YANG BERASOSIASI DENGAN SPONS Aplysina sp. PENGHASIL SENYAWA ANTIMIKROB ASAL PULAU ENGGANO

Abstract: Pulau Enggano merupakan salah satu pulau terluar di Indonesia yang memiliki keragaman biota yang cukup tinggi, salah satunya adalah hewan spons. Spons adalah sekelompok hewan multiseluler, memiliki ciri tubuh berpori, dan organisme invertebrata berguna dalam memproduksi senyawa bioaktif. Bakteri yang terkait dengan spons dapat menjadi sumber alternatif senyawa bioaktif baru, terutama antimikrob. Penelitian ini bertujuan untuk mengetahui potensi bakteri yang terkait dengan Aplysina sp. asal Pulau Enggano sebaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…The results from previous screening showed that 16 isolates of bacteria were isolated [14]. Four bacterial isolates could produced antifungal compounds.…”
Section: Screening Of Bacteria Producing Anti-fungalmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from previous screening showed that 16 isolates of bacteria were isolated [14]. Four bacterial isolates could produced antifungal compounds.…”
Section: Screening Of Bacteria Producing Anti-fungalmentioning
confidence: 99%
“…collected from Enggano Island against Candida albicans. Based on research conducted by [14] that Aplysina sp. has antibacterial and antifungal compounds tested against pathogenic bacteria and yeast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aplysina sp. sponge samples were collected previous research have been done from the coastal waters of Dua Island, Enggano Island located in North Bengkulu Regency (Wibowo et al, 2020). The samples obtained were immediately carried out in the preparation.…”
Section: Aplysina Sp Sponges Collectionmentioning
confidence: 99%
“…Berdasarkan pernyataan tersebut bakteri yang bersimbiosis dengan Ptilocaulis marquezii dapat dijadikan sebagai sumber alternatif baru sebagai antibakteri dan juga ekstrak yang berasal dari Ptilocaulis marquezii seperti Aplysina sp. yang memiliki bakteri simbion berupa bacillus dan memiliki aktivitas antibakteri E.coli dan S. aureus (Wibowo et al, 2020).…”
unclassified